2018
DOI: 10.1016/j.ejogrb.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm disease in advanced ovarian cancer: Predictability of pre-operative imaging and safety of surgical intervention

Abstract: Diaphragmatic disease is often discovered in AOC. However, pre-operative assessment with CT imaging is not reliable in accurately detecting diaphragm involvement. Therefore, all patients with AOC should be regarded as in potential need for diaphragm surgery and their operation undertaken in cancer centres with adequate expertise in upper abdominal surgery. If there is a suspicion of diaphragm muscle invasion during diaphragmatic peritonectomy, the muscle should be partially resected. This will lead to potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…The resection of the diaphragm is reported by other authors to be safe and feasible in case of liver-diaphragmatic metastatic lesions in patients with ovarian cancer [15], previous researches reporting that the resection of the diaphragmatic disease is not increasing significantly the morbidity rates [16]; contrary to published reports, our results did not show statistical significance regarding the diaphragm resection during CRS in patients with ovarian cancer. According to our research, performed appendectomy resulted to be a statistically significant protective factor for recurrence in the first year after CRS and HIPEC, and also for death, previous published studies reporting that appendectomy is extremely appropriate for contributing to maximal cytoreduction in advanced ovarian cancer cases [17].…”
Section: Discussioncontrasting
confidence: 99%
“…The resection of the diaphragm is reported by other authors to be safe and feasible in case of liver-diaphragmatic metastatic lesions in patients with ovarian cancer [15], previous researches reporting that the resection of the diaphragmatic disease is not increasing significantly the morbidity rates [16]; contrary to published reports, our results did not show statistical significance regarding the diaphragm resection during CRS in patients with ovarian cancer. According to our research, performed appendectomy resulted to be a statistically significant protective factor for recurrence in the first year after CRS and HIPEC, and also for death, previous published studies reporting that appendectomy is extremely appropriate for contributing to maximal cytoreduction in advanced ovarian cancer cases [17].…”
Section: Discussioncontrasting
confidence: 99%
“…However, those are still preliminary outcomes and further studies are needed so as to designate the exact depth of spread to the surrounding tissues as well as the impact of this energy source in ovarian reserve. Given the fact that OC disseminates through the peritoneum surface, electrosurgical ablative methods and techniques with minimal penetration to the underlying tissue could be beneficial ensuring a lower morbidity as well as eradication of lesions identified in surgically demanding locations (9). Various types of energy sources such as monopolar ablation, CO 2 laser, argon beam plasma and plasma energy, have been proposed aiming at the complete resection of the malignant lesions while simultaneously reducing the lateral spread and penetration to the affected organs (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Upper abdominal disease is a frequent finding in numerous cases of advanced OC and has been attributed to diffuse peritoneal dissemination (8). Diaphragmatic involvement, especially of the right hemidiaphragm, has been reported at a range of 42 to 71% of the cases (9). Complete resection of the disease recognized in the diaphragm at the time of cytoreduction has been associated with favorable survival outcomes, as it has been shown that recurrent disease often appears as diaphragmatic residual lesions.…”
Section: Introductionmentioning
confidence: 99%
“…‘Ultra‐radical’ procedures have been used in isolation in other conditions with acceptable safety profiles, and the previous reviews of advanced surgical procedures at the PBGCC only observed significantly increased morbidity in patients who underwent multi‐visceral resections …”
Section: Discussionmentioning
confidence: 99%